Pongapin and Karanjin, furanoflavanoids of Pongamia pinnata, induce G2/M arrest and apoptosis in cervical cancer cells by differential reactive oxygen species modulation, DNA damage, and nuclear factor kappa‐light‐chain‐enhancer of activated B cell signaling. (5th March 2019) - Roy, Rituparna; Pal, Debolina; Sur, Subhayan; Mandal, Suvra; Saha, Prosenjit; Panda, Chinmay Kumar
Abstract : In this study, the antitumor activity of two furanoflavanoid derivatives, Pongapin and Karanjin, was evaluated in comparison with Plumbagin, a plant‐derived polyphenol with proven antitumor activity. The compounds differentially inhibit the growth of different cancer cell lines (most effective on HeLa cells), with very low inhibitory effect on the growth of normal mouse embryonic fibroblast cell line. Pongapin like Plumbagin could significantly increase the intracellular reactive oxygen species (ROS) in the HeLa cells by stabilization of nuclear factor of kappa light polypeptide gene enhancer in B‐cells inhibitor (I‐κB) expression and reduction of nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) expression. In contrast, Karanjin could decrease ROS level by inhibition of I‐κB degradation resulting restriction of NF‐κB nuclear translocation. Pongapin and Plumbagin significantly increased DNA damage‐induced p53 expression and p21 nuclear expression. However, Karanjin treatment showed low DNA damage with increased p53 expression. The compounds induced G2/M arrest and increase in SubG1 population, indicating induction of apoptosis. Apoptosis was further validated by acridine orange/ethidium bromide dual staining and terminal deoxynucleotidyl transferase dUTP nick‐end labeling assay in HeLa cells after treatment with the compounds. The compounds induced caspase‐dependent apoptosis through induction of Bax/Bcl‐2 ratio either through increased expression of Bax by Pongapin and Plumbagin or low expression of Bcl‐2 by Karanjin. Thus, Pongapin and Karanjin may be potential natural anticancer agents in the future, like Plumbagin.